Evaluating compliance in three-dimensional-printed polymeric vascular grafts compared to human arteries and commercial grafts in a mock circulation loop compliance in three-dimensional-printed polymeric vascular grafts - Hong, Weichen; Tewari, Vijay; Yu, Huidan; Chen, Jun; Sawchuk, Alan P. (JVS-vascular science, 2025)
Compliance mismatch between native arteries and prosthetic grafts contribute to complications such as neointimal hyperplasia and pseudoaneurysms, leading to reduced graft patency. Three-dimensional (3D) printing offers a promising solution by flexibly customizing mechanical properties using elastic polymers. This study investigates whether 3D-printed polymeric grafts can better replicate native arterial compliance compared with commercial prosthetic grafts. We conducted compliance tests on human aortoiliac arteries, polytetrafluoroethylene (PTFE) grafts, Dacron grafts, and 3D-printed arteries with BioMed Elastic Resin within a mock circulation loop. All samples shared controlled geometry and were tested under the same physiological flow conditions. Pressure waveforms and key hemodynamic parameters were recorded and analyzed. The 3D-printed graft demonstrated a compliance of 0.49 cm3/mmHg, more closely matching the human artery than PTFE (0.38 cm3/mmHg) and Dacron (0.45 cm3/mmHg). Its mean arterial pressure (82 ± 0.6 mmHg) and peak pressure (40 ± 0.7 mmHg) in the flow loop also aligned more closely with the native artery compared with conventional grafts. Standard prosthetic graft materials have remained relatively static, whereas there has been immense advancement in new polymer technology. These polymers can match the compliance of native vessels, theoretically reducing complications associated with traditional grafts, and future work should investigate their biocompatibility, durability, and clinical feasibility.